2021
DOI: 10.3390/ijms22094389
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasomes in Teleosts: Structures and Mechanisms That Induce Pyroptosis during Bacterial Infection

Abstract: Pattern recognition receptors (PRRs) play a crucial role in inducing inflammatory responses; they recognize pathogen-associated molecular patterns, damage-associated molecular patterns, and environmental factors. Nucleotide-binding oligomerization domain-leucine-rich repeat-containing receptors (NLRs) are part of the PRR family; they form a large multiple-protein complex called the inflammasome in the cytosol. In mammals, the inflammasome consists of an NLR, used as a sensor molecule, apoptosis-associated spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 111 publications
(203 reference statements)
1
14
0
Order By: Relevance
“…Generally, inflammatory responses are tightly regulated by the interaction between cytokine components; the activation of inflammatory responses is aimed at enhancing the antimicrobial capacity of immune cells, facilitating pathogen clearance, and assisting tissue repair mechanisms (Grayfer and Belosevic, 2012;Morimoto et al, 2021). In the current study, we found various cytokines and their putative receptors were significantly affected in the liver of medaka fed with dietary silkrose-BM.…”
Section: Changes In Cytokine-cytokine Receptor Interactionsmentioning
confidence: 50%
“…Generally, inflammatory responses are tightly regulated by the interaction between cytokine components; the activation of inflammatory responses is aimed at enhancing the antimicrobial capacity of immune cells, facilitating pathogen clearance, and assisting tissue repair mechanisms (Grayfer and Belosevic, 2012;Morimoto et al, 2021). In the current study, we found various cytokines and their putative receptors were significantly affected in the liver of medaka fed with dietary silkrose-BM.…”
Section: Changes In Cytokine-cytokine Receptor Interactionsmentioning
confidence: 50%
“…In human, caspase-1/4/5/8 and neutrophil elastase cleave GSDMD, while caspase-3 cleaves GSDME, and all these cleavages occur in the inter-domain linker region (Kayagaki et al, 2015;Shi et al, 2015;Rogers et al, 2017;Wang et al, 2017;Kambara et al, 2018;Orning et al, 2018). In contrast, different cleavage modes exist in the lower vertebrate teleost, which comprise more than half of all living vertebrate species and possess only GSDME and GSDMF (Hofmann, 2020;Morimoto et al, 2021). In zebrafish Danio rerio, two GSDME orthologs, designated GSDMEa and GSDMEb, are cleaved by caspase-3 and caspy2 (caspase-4/5 homolog), respectively, to induce pyroptosis (Li et al, 2020;Wang et al, 2020), while in tongue sole Cynoglossus semilaevis, GSDME-mediated pyroptosis is activated by caspase-1/3/7 (Jiang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…When the body is invaded by pathogens, inflammatory caspase is activated, which eventually leads to the lysis of GSDMs. GSDM-NTs perforate the cell membrane surface, thereby inducing lytic death of pathogens and infected host cells (1,2,6,7).…”
Section: Discussionmentioning
confidence: 99%
“…Gasdermin D (GSDMD) was first discovered in 2015 and was identified as the key executive protein of downstream molecular signals after the activation of caspase (4,5). The classical pyroptosis pathway is mediated by the assembly of inflammasomes, including NLRC4, NLRP1, NLRP2, NLRP3, NLRP6, NLRP7, and AIM2 (6,7). Inflammasomes and their related cytokines are also associated with the tumor immune microenvironment and prognosis (8,9).…”
Section: Introductionmentioning
confidence: 99%